Floating Macrophyte Control with Glyphosate According to Adjuvants and Spray Nozzles - Silva, A.f. [UNESP] (2018)
The goals of this study were to evaluate the application of glyphosate plus three adjuvants and three spray nozzles in controlling the macrophyte Pistia stratiotes. For this purpose, after an 80 to 90% colonization, the application of 1.5, 3.5 and 7.0 L h-1 of isolated glyphosate and with the adjuvants Aterbane® BR, Veget’oil® and Dash® HC (0.5% vv-1) and the spray nozzles (AI 110.02, TTI 110.015 and TT 110.015) was performed, plus a control sample (water). Applications were performed with a pressurized backpack precision sprayer, at the constant pressure of 50 p.s.i. and with mixture consumption of 200 L ha-1. At the dose of 1.5 L ha-1, there was 100% control for the combination glyphosate + Veget’oil + tip AI 110.02 (Gly+V.oil+AI, Gly+Aterb.+TTI and Gly+Dash+TT) 15 days after application (DAA). At 3.5 L ha-1, the greatest control (95%) was with Gly+AI, Gly+Aterb.+TTI, Gly+V.oil+TTI, Gly+Dash+TTI, Gly+Aterb.+TT and Gly+Dash+TT; and at 7.0 L ha-1 100% was observed for Gly+AI, Gly+Aterb.+AI, Gly+V.oil+AI, Gly+Aterb.+TTI, Gly+V.oil+TTI, Gly+Dash+TTI, Gly+TT and Gly+Dash+TT. Thus, it is possible to conclude that at 1.5 L ha-1, the combination of glyphosate plus Dash® and with the nozzle TT 110.015 (Gly+Dash+TT) was the most promising one; at 3.5 L ha-1, it was Gly+Aterb.+TTI and at 7.0 L ha-1 the air induction nozzles (AI 110.02 and TTI 110.015), whether with isolated glyphosate or with any of the three adjuvants, were the best at providing control.